2017
DOI: 10.3892/ol.2017.6745
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-30a-5p suppresses proliferation, invasion and tumor growth of hepatocellular cancer cells via targeting FOXA1

Abstract: Abstract. Deregulation of microRNAs (miRs) has been observed in a variety of types of human cancer. Previously, miR-30a-5p has been demonstrated to exhibit a suppressive role in hepatocellular carcinoma (HCC). However, the underlying mechanism remains largely unclear. The present study aimed to elucidate the regulatory mechanism of miR-30a-5p in proliferation and invasion of HCC cells. Quantitative reverse transcription polymerase and western blotting were used to examine mRNA and protein expression of Forkhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The function of miR-30a-5p in other cancers has been widely investigated. MiR-30a-5p has been identified as a tumor suppressor in hepatocellular cancer (23), renal cell carcinoma (24), small cell lung cancer (25), upper tract urothelial carcinoma (26), gastric cancer (27) and breast tumor (28). Moreover, Wei et al (29) indicated that miR-30a-5p suppresses tumor metastasis of human colorectal cancer by targeting ITGB3.…”
Section: Discussionmentioning
confidence: 99%
“…The function of miR-30a-5p in other cancers has been widely investigated. MiR-30a-5p has been identified as a tumor suppressor in hepatocellular cancer (23), renal cell carcinoma (24), small cell lung cancer (25), upper tract urothelial carcinoma (26), gastric cancer (27) and breast tumor (28). Moreover, Wei et al (29) indicated that miR-30a-5p suppresses tumor metastasis of human colorectal cancer by targeting ITGB3.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this miRNA could indirectly imply to the dysregulated physiological conditions resulting in implantation failure and serves as a potential minimally invasive biomarker in this regard. miR-30a-5p acts as a tumour suppressor by inhibiting cell proliferation and invasion [61,62,63]. In blood cells, miR-30a takes part in the regulation of erythrocyte maturation [64].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors claimed that miR-132 acts as a tumor suppressor targeting FOXA1 in thyroid papillary carcinoma [23]. Similarly, in other human diseases, FOXA1 expression has been found to be inhibited by miR-30a-5p and miR-212 in hepatocellular carcinomas [24,25], by miR-212 in osteosarcomas [26], by miR-194 in non-small cell lung cancers [27], and by miR-431 in necrotizing enterocolitis [28]. The current study included only one case of undifferentiated sarcoma of the thyroid.…”
Section: Discussionmentioning
confidence: 99%